Effect of astaxanthin supplementation on oxidative stress in adult women with polycystic ovary syndrome: a systematic review and meta-analysis of randomized controlled trials - Donna Pratiwi; Agustinus I Wayan Harimawan; I Wayan Weta; Ni Ketut Sumartini; Syuma Adhy Awan; I Wayan Gede Sutadarma (Universa Medicina, 2026)
BackgroundPolycystic ovary syndrome (PCOS) can cause significant morbidity through fertility disorders and most often found in the productive age. Recent research suggests that oxidative stress plays an important role in the pathogenesis of PCOS. Astaxanthin (AST) has broad protective effects, particularly in the regulation of antioxidant and anti-inflammatory activity. The objective of this systematic review and meta-analysis was to evaluate the efficacy of AST supplementation on PCOS management. MethodsA systematic literature search was conducted in PubMed, Scopus, Science Direct, and Cochrane Library from January 2020 to March 2025. Randomized controlled trials (RCTs) assessing astaxanthin supplementation in adult women with PCOS were included. Outcomes of interest were malondialdehyde (MDA), superoxide dismutase (SOD), and total antioxidant capacity (TAC). Data were analyzed using Review Manager (RevMan) version 5.4.1. Pooled effects were calculated as mean differences (MDs) with 95% confidence intervals (CIs).  ResultsFour RCTs involving 194 participants were included. Astaxanthin supplementation significantly reduced MDA levels (MD −0.670; 95% CI −1.070 to −0.270; p = 0.001; I² = 93%) and significantly increased TAC levels (MD 0.030; 95% CI 0.000 to 0.060; p = 0.030; I² = 76%). No significant effect was observed on SOD levels (MD 0.025; 95% CI −0.850 to 1.350; p = 0.660; I² = 57%). The overall risk of bias across included studies was low. ConclusionThis systematic review shows that AST supplementation significantly reduced lipid peroxidation in women with PCOS. These findings suggest that AST may serve as potential adjuvant antioxidant therapy in PCOS management.